Introduction. The Mediality of Concealment: Material Practices and Symbolic Operativity - Casemajor, Nathalie; Toupin, Sophie (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2018)
This special issue focuses on the cultural forms, technologies, and social logics of dissimulation. In this introduction, we propose a critical examination of the cultural and political entanglements of three emblematic domains of dissimulation: camouflage, steganography, and encryption. Focusing on the study of mediality, our analysis crosses the evolution of media environments and representations of these dissimulation processes to better understand their modes of legitimization and symbolic operativity.